2019
DOI: 10.3389/fevo.2019.00102
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Trophic Species Interactions Shape Seascape-Scale Coral Reef Vegetation Patterns

Abstract: How species interactions shape habitat structure is a longstanding question in ecology. A curious phenomenon reflecting ecological self-organization around reef habitat structures exists on coral reefs: large-scale (hundreds to hundreds of thousands of m 2) halo-like patterns surrounding patch reefs, i.e., individual coral reefs that are often separated by seagrass or macroalgal meadows. These "halos," long known to occur in various locations worldwide, reflect a distinct band of unvegetated sediments surround… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…The maximum distance that by halo-feeding herbivores ventured from the reef was unrelated to their relative abundance ( z = 1.66, p = 0.096; fig. 2A in Madin et al [8]). We found that piscivores likewise concentrated their time on and immediately around the reef, but, unlike herbivores, were also found throughout the halo zone and beyond its boundary into the algal meadows (figure 1 b ; red bars).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum distance that by halo-feeding herbivores ventured from the reef was unrelated to their relative abundance ( z = 1.66, p = 0.096; fig. 2A in Madin et al [8]). We found that piscivores likewise concentrated their time on and immediately around the reef, but, unlike herbivores, were also found throughout the halo zone and beyond its boundary into the algal meadows (figure 1 b ; red bars).…”
Section: Resultsmentioning
confidence: 99%
“…These mechanisms are not mutually exclusive with one another, nor with herbivory. For example, in our in situ study system of Heron Island lagoon, there is some evidence that bioturbation may contributing to halo formation along with the recognized key direct mechanism of herbivory [8]. Similarly, surface sediment particle size does vary significantly with distance from patch reefs [14] within Heron Island lagoon but was not found to have an effect on algal canopy height over the halo gradient [6].…”
Section: Introductionmentioning
confidence: 99%
“…Camera traps remotely record still or video imagery of animals in their natural habitat. Given that they are small and stationary, camera traps are well suited to the generation of data on the presence, diversity, distribution and behaviour of mobile species that is largely free of human influence (e.g., Madin et al, ). Like drones, camera traps can be deployed at depth and have been instrumental in improving our understanding of both the pelagic zone and the deep sea (e.g., Jamieson et al, ).…”
Section: Design Of a Macroscopementioning
confidence: 99%
“…Night‐time studies are particularly problematic: infrared radiation, which is invisible to fishes and needed for unobtrusive illumination, does not penetrate water. Extremely low‐light‐sensing cameras paired with far‐red illumination that is invisible to most fishes might help (Madin et al, ). Lastly, marine environments typically have low contrast and constant movement of particles, rendering automated image processing difficult, but not impossible (Villon et al, ).…”
Section: Design Of a Macroscopementioning
confidence: 99%
“…The field component of this project took place at Heron Island on Australia's southern Great Barrier Reef. The aim of the project was to determine the ecological mechanisms responsible for the formation of landscape-scale vegetation patterns surrounding coral reefs known as reef "halos" (Madin et al, 2019). In order to achieve this aim, it was necessary to obtain and process satellite imagery with specific characteristics.…”
Section: Conclusion: Moving Forward and Scaling Upmentioning
confidence: 99%